Draft Genome Sequences of Seven Cronobacter sakazakii Strains Carrying the mcr 9.1 Gene Isolated in Chile - Parra-Flores, Julio; Holý, Ondrej; Riffo, Francisca; Lepuschitz, Sarah; Ruppitsch, Werner; Forsythe, Stephen (Microbiology resource announcements, 2021)
Cronobacter sakazakii is a pathogen that causes severe diseases such as meningitis and necrotizing enterocolitis in infants under 12 months, associated with the consumption of contaminated rehydrated powdered infant formula (PIF). We present seven C. sakazakii genome sequences isolated from PIF and dairy products in Chile in 2017.